MiR-147: Functions and Implications in Inflammation and Diseases - Lin, Ling; Hu, Kebin (MicroRNA, 2021)
MicroRNAs (miRNAs) are small non-coding RNAs (19 25 nucleotides) that regulate gene expression at a post-transcriptional level through repression of mRNA translation or mRNA decay. MiR-147, which was initially discovered in mouse spleen and macrophages, has been shown to correlate with coronary atherogenesis and inflammatory bowel disease and modulate macrophage functions and inflammation through TLR-4. Altered miR-147 level has been shown in various human diseases, including infectious disease, cancer, cardiovascular disease, neurodegenerative disorder, etc. This review will focus on the current understanding regarding the role of miR-147 in inflammation and diseases.
Keywords: neurodegenerative disorder